Analysis of Grammatical Morpheme Acquisition of Indonesian High School English Learners - Purnamaningwulan, Rina Astuti (Indonesian Journal of English Language Studies (IJELS), 2020)
L2 learners’ morpheme acquisition has been studied a lot subsequent to Dulay and Burt’s work (1974). Similar to other studies responding to Krashen’s (1977) notion on natural acquisition order, this small-scale research aims at investigating whether Indonesian high school English learners also go through similar acquisition order as the respective notion. The data taken from a group of Indonesian high school students’ writing assignment were analyzed using the Obligatory Occasion Analysis (Ellis & Barkhuzien, 2005) to investigate the grammatical morpheme acquisition order of the students. Subsequently, the finding was analyzed to see whether the acquisition order was influenced by Krashen’s hypothesis. The findings showed that the morpheme acquisition order of the research participants did not go through similar acquisition order as stated in Krashen’s natural order hypothesis. Further, the participants’ L1 partially contributed to the order.